Feeding on infinity : readings in the romantic rhetoric of internalization - Wilner, Joshua (Johns Hopkins University Press, 2000)
"Notions of "internalization" play an important role in many contemporary fields of discourse, including literary history and theory, psychoanalysis, ideological critique, and learning theory in the social sciences. But the meaning of this term and the continuities and discontinuities at work in its varied deployment have, for the most part, gone unanalyzed." "In Feeding on Infinity, Joshua Wilner explores the power and limits of the discourse of internalization through the close reading of a variety of texts drawn from the Romantic tradition, a tradition which is both source for and often times object of this discourse. Through the study of writers including Rousseau, Wordsworth, De Quincey, Baudelaire, Freud, Benjamin, and Sedgwick, he seeks to deepen our understanding of the problem of internalization, while situating its more or less explicit emergence as a problem in relation to the history of, in Gertrude Stein's phrase, "patriarchal poetics.""--Jacket.